PENGARUH VARIASI PUTARAN SPINDLE TERHADAP WAKTU DAN BIAYA PROSES PRODUKSI PENINGGI SHOCK BREAKER DEPAN PADA MESIN CNC TU-2A DENGAN MATERIAL ALUMINIUM 6061 - Eli Novita Sari; Yusfi Ihza Rizaldi; Siti Duratun Nasiqiati Rosady; M Fauzi Soulton (Politeknik Negeri Banyuwangi, 2023)
The development of science and technology is in balance with the development of industrial technology. The development of this technology is evidenced by the invention of the CNC machine which is a machine tool that is controlled using a numerical control system. The purpose of this study was to find the effect of variations in spindle rotation on the time and cost of the production process for increasing the front shock breaker on a TU-2A CNC machine with 6061 aluminum material. and conclusion. From the results of this study it can be concluded that: (1) There is an influence of variations in spindle rotation, namely at 1,700, 2,200 and 2,700 rpm the resulting production time for increasing the front shock breaker is 25.87, 25.9 and 26.03 minutes/product, respectively. (2) There is an effect of variations in spindle rotation, namely at 1,700, 2,200 and 2,700 rpm, the production cost of increasing the front shock breaker respectively is Rp. 230,347,-; Rp. 230.368,-; Rp. 230,388, - / product. (3) Variation of spindle rotation that results in the lowest production time and costs is work with a spindle rotation of 1,700 rpm, which is 25.87 minutes/product and costs Rp. 230,347,- / product. Keywords: Heightening shock breaker, spindle rotation, total time and cost